A Glymphatic System and New Etiopathogenic Hypothesis on Glaucoma Patients Who Underwent Osteopathic Manipulative Treatment: A Pilot Study - Paoli, Daniela; Michelin, Leonardo; Vassallo, Fabrizio (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Purpose Malfunction of the lymphatic or glymphatic system recently shown in the brain, seems to play an important role in central neurodegenerative pathologies through a build-up of neurotoxins. Recent studies have shown functional links between aqueous humour and cerebrospinal fluid via the glymphatic system, offering new perspectives and unifying theories on the vascular, biomechanical and biochemical causes of chronic and openangle glaucoma (POAG). The aim of this randomized pilot study is to compare the variations in intraocular pressure between 20 cases of compensated POAG under pharmacological therapy and 20 glaucoma patients undergoing osteopathic treatment, hypothesizing that this manipulation can influence intraocular pressure. Materials and Methods The 40 patients under study, all covered by the Helsinki convention, were randomly divided into 2 groups (treated group or TG and control group or CG). The 40 patients were chosen from compensated glaucoma sufferers, who required neither changes in therapy nor operations which would affect their eye pressure which was measured both before and after manipulative osteopathic treatment scheduled into 4 sessions at intervals of 7.3 and 150 days, then compared with the control group (20 patients) who were undergoing pharmacological treatment only. Results The average IOP in the TG was compared with the CG throughout the entire treatment cycle showing a statistically inconclusive reduction in the right eye RE P-value (0.0561), while for the left eye a significant effect was shown LE (0.0073). The difference between the reduction in IOP between TG and CG was observable 10 months after the first session or rather 5 months after the last, and demonstrable during a check-up 13 months after the beginning of the study, or rather 8 months in absence of treatment with a highly significant statistical p-value (0.000434). Conclusions This study has shown that manipulative osteopathic treatment can affect intraocular pressure after each session and that the pressure is significantly lower even months after the last treatment session.